From Scott to Cooper: Sedgwick’s Hope Leslie as a revisionist history of Women in the Puritan& Patriarchal American Colonial Frontier - Gassim, Fatima (Gezira Journal of Educational Sciences and Humanities; Vol 12 No 2 (2015), 2018)
This paper focuses on the feminist discourse in the historical novel as exemplified by Hope Leslie, a nineteenth –century historical novel written by a woman novelist, Catherine Sedgewick. The study presents an analytical reading of  the novel as a conventional historical novel following the steps of the British Scott and the American Cooper.  In the light of the Lukacs’s in The Historical Novel, the study discuses some of the historical features in the novel, and approaches the narrative technique that distinguished Sedgwick’s revisionist reading of history as a woman, and her portrayal of the revolutionary woman who resists of  patriarchy in the American colonial frontier. The study concludes that the narrative structure of Hope Leslie, like that of Scott and Cooper is based on a new vision of the past, and an emphasis on understanding of the new meanings in history. Undoubtedly, the nineteenth-century novelists succeeded in unveiling the sequence of moral and cultural conflicts throughout history. And female novelists like Catherine Sedgwick ,have inspired generations of marginalized women. Heroines like “Hope” and Megawiska and planted the suppress champions women such as "magawiska"  have planted hope in in a better future in the hearts of the suppressed and marginalized women of the next generations